Design & Development of a Screw Conveyor-Based Soybean Washing Machine for Tempeh Production - Zoel Fachri; Rouhillah; Muharrir Alwathani (UIR PRESS, 2023)
Soybeans are one of the main ingredients for making tempeh. Most of the tempeh production businesses still use the traditional system of washing soybeans. Washing soybeans is still done manually using a washing drum filled with water and stirred by hand, thus draining the workforce. In the process of washing soybeans, there is still direct contact with parts of the human body, resulting in unhygienic soybeans. From these problems, the solution is to make a machine that can wash soybeans in tempeh production which aims to facilitate washing soybeans and produce clean and hygienic soybeans. The soybean washing machine process uses a screw conveyor system with an AC motor 1 phase 1 HP 1420 Rpm as a driving force and a DC 12 V 25 W water pump to drain water into the watering canal. The machine can wash 5 kg of soybeans for 10 seconds, and produces a motor rotation of 271.2 Rpm, voltage 229 V, current 2.58 A to produce clean and hygienic soybeans.